2005
DOI: 10.1016/j.neuroimage.2005.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Myelination and long diffusion times alter diffusion-tensor-imaging contrast in myelin-deficient shiverer mice

Abstract: Diffusion tensor imaging (DTI) using variable diffusion times (t diff ) was performed to investigate wild-type (wt) mice, myelin-deficient shiverer (shi) mutant mice and shi mice transplanted with wt neural precursor cells that differentiate and function as oligodendrocytes. At t diff = 30 ms, the diffusion anisotropy "volume ratio" (VR), diffusion perpendicular to the fibers (λ ⊥ ), and mean apparent diffusion coefficient (〈D〉) of the corpus callosum of shi mice were significantly higher than those of wt mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
100
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 53 publications
(66 reference statements)
18
100
0
Order By: Relevance
“…The FA values for the corpus callosum reported here from both ROI and fiber tracking analyses fall within the range of published values in rodents from ROI analysis (range: 32 to 75%) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005). The few studies in humans that have compared diffusion parameters calculated from fiber tracking and ROI analysis reveal that FA values obtained using the former method tend to be lower (Dubois, et al, 2006;Thomas, et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The FA values for the corpus callosum reported here from both ROI and fiber tracking analyses fall within the range of published values in rodents from ROI analysis (range: 32 to 75%) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005). The few studies in humans that have compared diffusion parameters calculated from fiber tracking and ROI analysis reveal that FA values obtained using the former method tend to be lower (Dubois, et al, 2006;Thomas, et al, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…To date, the mainstay of diffusion imaging studies of the rodent brain have used high-field animal scanners (4.7-11.7T) (Guilfoyle, et al, 2003;Harsan, et al, 2006;Hoehn-Berlage, et al, 1999;Nair, et al, 2005;Tyszka, et al, 2006;Verma, et al, 2005;Zhang, et al, 2002). Additionally, because adequate signal-to-noise ratio (SNR) requires prolonged scan times, many of these experiments have been conducted on in vitro brain tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that an increment of axial diffusivity ( 2 and 3 ) is related to myelin deficiency, whereas a decrease of parallel diffusivity ( 1 ) indicates axonal disturbance. [26][27][28] Our findings of higher values for 2 and 3 indicate that diffusion perpendicular to the white matter structure is higher. Because we did not find lower values for 1 in NF-1 regions with UBOs than in NF-1 regions without UBOs, we hypothesize that the observed changes of the brain tissue in NF-1 are not caused by damage to the axon, but relate to myelin deficiency.…”
Section: Discussionmentioning
confidence: 54%
“…DTI is likely to have similar properties in humans and experimental animals, as shown by comparisons between humans with multiple sclerosis and animal models of demyelinating diseases (Bammer et al, 2000;Filippi et al, 2001;Kim et al, 2006;Song et al, 2005). This method has been used to detect white matter pathology in experimental animal models of neurological diseases (Gaviria et al, 2006;Gulani et al, 2001;Nair et al, 2005;Ono et al, 1995;Song et al, 2004;Song et al, 2003;Song et al, 2005), including traumatic spinal cord injury (Deo et al, 2006;Nevo et al, 2001;Schwartz et al, 2005) by exploiting its sensitivity to white matter orientation. It can provide information about brain microstructure by quantifying isotropic and anisotropic water diffusion (Huisman et al, 2003;Neil et al, 2002;Sundgren et al, 2004).…”
Section: Introductionmentioning
confidence: 99%